Suppression and treatment of Haloperidol induced extra-pyramidal side effects and anxiety syndrome by the coadministeration of red rice bran oil in rats - Naz, Farah; Erum Shireen (International Journal of Endorsing Health Science Research, 2014)
Antipsychotic medications may reduce or eliminate symptoms of psychosis. They are not a 'cure' for mental illnesses, but can be an effective part of treating mental disorders. Even though many of the antipsychotics such as haloperidol cannot cure mental illnesses, they are effective in eliminating or reducing psychotic symptoms. However, prolong administration of haloperidol may result in parkinsonian like effects and tardive dyskinesia. The objective of the present research was to determine the effects of long term co-administration of RRBO in diet on haloperidol induced anxiety and EPS. It was hypothesized that co-administration of RRBO by the free radicals scavenging property could alleviate parkinsonian like effects and tardive dyskinesia. The present results showed a reversal of haloperidol induced parkinsonian like effects and tardive dyskinesia in rats cotreated with RRBO.